Fractional statistics description applied to adsorption of alkane binary mixtures in zeolites - Davila, Mara Veronica (2009)
In the present paper, the multicomponent adsorption of polyatomic species is described as a fractional statistics problem, based on Haldane's statistics. Site exclusion is characterized by a "mutual exclusion matrix" g, which relates to the sizes of the different species and lattice geometry. The adsorption process has been monitored through total and partial isotherms, energy of adsorption and configurational entropy of the adsorbed phase. The thermodynamic functions calculated for a monomer-dimer mixture were applied to describe the adsorption of methane-ethane mixtures in zeolites. In the case of zero lateral interactions, the present approach was compared to the well-known ideal adsorbed solution theory. The results show that the treatment of this complex problem can be significantly simplified if looked up from the new theoretical perspective.